EQUITY IN THE DISTRIBUTION OF SANITARISTS FORMED TO WORK ON SUS - Ferreira, Joel Saraiva; Filgueiras, Ana Rita Barbieri; Cazola, Luiza Helena Oliveira (Journal of Health Care, 2018)
Introduction: The qualification of sanitarians to perform on the National Health System (SUS) representan important action for the formulation and development of public policies. However, such professionalsneed to be present in the several municipalities, including those where human development conditions areless favourable. Objective: To analyse the distribution equity of qualified sanitarians in Mato Grosso doSul, from 2008 to 2013, in the public health service, considering the Human Development Index (HDI)of the municipality where they resided and worked. Methods: this is a descriptive study with quantitativeapproach, using secondary data of the register of graduates of specialisation courses on public health,developed by the Health Department of the State of Mato Grosso do Sul. From that database, the variablesof interest were extracted: gender, occupation, residing municipality, distribution of professionals byhealth region and by HDI stratum. Results: In the period, three specialisation courses on public healthwere held, totalising 61 sanitarians, coming from 20 out of the 79 state’s municipalities. There was a prevalenceof female gender (83.6%), nursing occupation (29.5%), and professionals who reside and workin the health region of Campo Grande (70.5%), the most populous city, with the best HDI in the state,prevailed. Conclusion: The results suggest that there are difficulties to guarantee the distribution equityof sanitarians in the SUS in Mato Grosso do Sul, since the qualification and the location for professionalexercise are not articulated to supply the health demand of municipalities with smaller HDI.